2017
DOI: 10.1007/s00221-017-5006-4
|View full text |Cite
|
Sign up to set email alerts
|

Moving higher and higher: imitators’ movements are sensitive to observed trajectories regardless of action rationality

Abstract: Humans sometimes perform actions which, at least superficially, appear suboptimal to the goal they are trying to achieve. Despite being able to identify these irrational actions from an early age, humans display a curious tendency to copy them. The current study recorded participants’ movements during an established imitation task and manipulated the rationality of the observed action in two ways. Participants observed videos of a model point to a series of targets with either a low, high or ‘superhigh’ trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 63 publications
6
15
2
Order By: Relevance
“…Whilst meaningless action imitation may be more reliant on kinematic processing (Buxbaum et al ., ), kinematic information might still be relevant to the way in which one must replicate a meaningful action. To take an extreme example, the imitator is not likely to ignore explicit but irrelevant kinematics, such as a particularly slow or rapid action which does not assist in the development of the final posture (see Forbes & Hamilton, , for evidence that possibly supports this).…”
Section: Discussionsupporting
confidence: 72%
“…Whilst meaningless action imitation may be more reliant on kinematic processing (Buxbaum et al ., ), kinematic information might still be relevant to the way in which one must replicate a meaningful action. To take an extreme example, the imitator is not likely to ignore explicit but irrelevant kinematics, such as a particularly slow or rapid action which does not assist in the development of the final posture (see Forbes & Hamilton, , for evidence that possibly supports this).…”
Section: Discussionsupporting
confidence: 72%
“…The fact that similar effects as in Experiment 1 were observed when co-actors could not see each other’s actions is crucial in that it distinguishes the present findings from earlier findings on automatic imitation of action sequences (e.g., Forbes and Hamilton, 2017 , Pan and Hamilton, 2015 ; for a recent meta-analysis on automatic imitation, see Cracco et al, 2018 ). In the latter studies, it was tested whether participants’ own performance of an action sequence is affected by prior observation of a (virtual) actor performing the same or a different action sequence.…”
Section: Methodssupporting
confidence: 72%
“…For example, participants first watched an actor in a video perform three consecutive taps on three different drums; then participants tapped their own three drums either in the same or in a different order as the actor ( Pan & Hamilton, 2015 ). In another study ( Forbes & Hamilton, 2017 ), participants first observed an actor perform a series of three target-directed pointing movements in the presence or absence of obstacles between the targets. Afterwards, participants pointed to the same targets as the actor but there were no obstacles between the targets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst previous work has quantitatively examined the kinematic elements of imitative behavior in both healthy people (e.g., Braadbaart et al, 2012;Campione & Gentilucci, 2011;Era et al, 2018;Forbes & Hamilton, 2017;Gold et al, 2008;Hayes et al, 2016;Krüger et al, 2014;Pan & Hamilton, 2015;Reader & Holmes, 2015;Reader et al, 2018;Sacheli et al, 2012;Sacheli et al, 2013, Sacheli, Christensen, et al, 2015Wild et al, 2010;Williams et al, 2013) and brain-damaged patients (e.g., Candidi et al, 2018;Hermsdörfer et al, 1996), as far as we are aware no previous experiments have looked at so many components of the velocity profile in order to compare the coarse-grained (i.e., wrist) kinematic approach to meaningful and meaningless action imitation. Much informative work has been done to assess action performance in meaningful and meaningless action imitation (e.g., Buxbaum et al, 2014;Goldenberg & Hagmann, 1997;Mengotti et al, 2013), but frequently using only subjective rating measures.…”
Section: Kinematics In Meaningful and Meaningless Action Imitationmentioning
confidence: 99%